Pengaruh Promosi Terhadap Kepuasan Pelanggan Di PT Electronic City Cabang Pamulang: INFLUENCE OF PROMOTION TOWARDS CUSTOMER SATISFACTION - Ibrohim; Agi Nugraha; Rizky dan Agi, Rizky hidayah (Indonesian Journal Entrepreneurship Finance and Business Management, 2024)
This research was conducted from December 2022 to May 2023. The research objective was to generate information in the form of a more in-depth  explanation  about  the  influence  of  promotion  on  customer satisfaction and to obtain results from data processing on the extent of the influence of promotion on customer satisfaction. The method used was causality or cause-and-effect with the influence method. The type of  research  was  descriptive  and  verificative  with  a  population  and sample  of  95  customer  respondents,  using  field  studies  and  direct surveys through questionnaire distribution. The result of the simple linear regression equation between X and Y is Y=9.481+0.638+e.  The  results  of  Hypothesis  Testing  show  that  the Promotion  variable  has  a  sig  value  <  0.05,  meaning  it  is  significant. tcount=9.269  >  ttable=1.6610.  Thus,  the  Promotion  variable  has  a positive   and   significant   relationship   with   Customer   Satisfaction. Therefore,   the   hypothesis   test   result:   H1   is   accepted   and   H0   is rejected. The correlation coefficient obtained is r=0.693, which means there is a strong and positive relationship indicating that an increase in Promotion can generally increase Customer Satisfaction. The result of KD (R²) = 0.480. This means that 48% of the independent variable, Promotion, can explain Customer Satisfaction. The remaining 52% is explained by other factors not examined in this study.